'Replacement Care' for Working Carers? A Longitudinal Study in England, 2013–15. (16th August 2017) - Pickard, Linda; Brimblecombe, Nicola; King, Derek; Knapp, Martin
Abstract: In the context of rising need for long‐term care, reconciling unpaid care and carers' employment is becoming an important social issue. In England, there is increasing policy emphasis on paid services for the person cared for, sometimes known as 'replacement care', to support working carers. Previous research has found an association between 'replacement care' and carers' employment. However, more information is needed on potential causal connections between services and carers' employment. This mixed methods study draws on new longitudinal data to examine service receipt and carers' employment in England. Data were collected from carers who were employed in the public sector, using self‐completion questionnaires in 2013 and 2015, and qualitative interviews were conducted with a sub‐sample of respondents to the 2015 questionnaire. We find that, where the person cared for did not receive at least one 'key service' (home care, personal assistant, day care, meals, short‐term breaks), the carer was subsequently more likely to leave employment because of caring, suggesting that the absence of services contributed to the carer leaving work. In the interviews, carers identified specific ways in which services helped them to remain in employment. We conclude that, if a policy objective is to reduce the number of carers leaving employment because of caring, there needs to be greater access to publicly‐funded services for disabled and older people who are looked after by unpaid carers.